Prognostic value of platelet to lymphocyte ratio in patients with cervical cancer: an updated systematic review and meta-analysis - Tianyu Zhu; Zhaoying Chen; Beichen Zhang; Xianqing Wu (World Journal of Surgical Oncology)
Abstract Background The identification of biomarkers that reliably forecast cervical cancer (CC) outcomes is a key area of research. Several studies have explored the link between the platelet-to-lymphocyte ratio (PLR) and cervical cancer prognosis, though the results are not entirely conclusive. Methods PubMed, Embase, Web of Science, and the Cochrane Library were used to search, with studies published up to May 30, 2024. The selection of studies followed predetermined inclusion and exclusion criteria. Overall survival (OS), progression-free survival (PFS), and disease-free survival (DFS) were primary outcomes. Hazard ratios (HR) and 95% confidence intervals (CIs) were calculated. Sensitivity and subgroup analyses were performed to evaluate the stability and investigate potential heterogeneity. Review Manager version 5.4.1 and STATA version 15.0 were conducted to analyze. Results Thirty cohort studies, involving 8,597 patients, were included. The pooled data showed that a higher PLR was associated with worse OS significantly (HR = 1.77, 95% CI: 1.43–2.19; p < 0.0001), PFS (HR = 1.69, 95% CI: 1.26–2.27; p = 0.0004), and DFS (HR = 1.57, 95% CI: 1.12–2.18; p = 0.008). Subgroup analysis indicated that the prognostic relevance of PLR was most prominent in patients who underwent both surgery and radiotherapy, as well as those from Asia and the America. Furthermore, a PLR threshold above 150 was associated with improved predictive accuracy. Conclusion Increased PLR among cervical cancer patients was significantly correlated with reduced OS, PFS, and DFS, pointing to its potential role as an independent prognostic marker. Nonetheless, additional prospective research is required to verify this finding.